Predictors of Carotid Artery Stenting-Induced Hemodynamic Instability. (July 2021) - Saleh, Mahmoud; Ali, Haitham; Atalla, Khaled; Shahat, Mohammed; Cieri, Enrico
Background: To address the predictors of hemodynamic instability (HI) related to carotid artery stenting (CAS) and evaluate the association between HI and periprocedural adverse outcomes. Methods: This study comprised all consecutive patients who underwent CAS for atherosclerotic carotid artery stenosis from March 2014 to May 2018. A standardized dose of atropine (0.4 mg) was given prior to stent deployment. Changes in heart rate, blood pressure, and neurological status were monitored and recorded. Potential predictors of HI were tested in multivariate analysis using binary logistic regression model. Results: A total of 728 patients were enrolled. Two hundred twenty seven patients (31.2%) developed periprocedural HI. The presence of hypertension (OR, 2.037; 95% CI, 1.292-3.211; P = 0.0022), symptomatic carotid lesions (OR, 1.704; 95% CI, 1.057-2.747; P = 0.0287), right sided lesions (OR, 3.090; 95% CI, 1.934-4.935; P ≤ 0.0001), hyperechoic/calcified plaques (OR, 2.195; 95% CI, 1.458-3.304; p P = 0.0002), and longer lesions (OR, 1.043; 95% CI, 1.012-1.076; P = 0.0072) were significant predictable factors for the occurrence of HI. On the other hand, smoking was significantly associated with a 48.1% decrease in risk of development of HI (OR, 0.519; 95% CI, 0.358-0.754; P = 0.0006). There were no statistically significant differences in periprocedural morbidity or mortality between patients with and without HI. Conclusion: HI occurs in a considerable percentage of patients undergoing CAS. Hypertension, right sided, symptomatic carotid lesions, calcified plaques, and longer lesions were shown to be independent risk factors for the development of periprocedural HI. Conversely, smoking demonstrated a protective effect. HI did not appear to predispose to periprocedural adverse events.